Biochar and its twin benefits: Crop residue management and climate change mitigation in India. (March 2022) - Anand, Abhijeet; Kumar, Vivek; Kaushal, Priyanka
Abstract: Crop residue management remains a major problem in the Indian agriculture sector. The in-situ firing of crop residues has been linked to air pollution, global warming, soil fertility decline and others. Biochar conversion through slow pyrolysis could be one of the techniques for the safe disposal of crop residues. 212.04 ± 44.27 MT biochar could be produced from 517.82 MT crop residues in India. Biochar conversion of crop residues can address agriculture production, safe drinking water, livelihood, energy security and environmental protection. Soil amendment with biochar sequestrate about 376.11 ± 78.52 MT CO2 e carbon and help retain about 1.66 ± 0.46 MT of soil nutrients. Also, crop residues derived biochar has an estimated market value of approximately 500 billion in India. Biochar applications in the cosmetics, pharma and chemical industries offer market and employment opportunities. This review discusses the impact of in-situ crop residue burning and its biochar conversion through slow pyrolysis as part of sustainable crop residue management. Also, biochar applications and socio-economic aspects of crop residues – biochar system has been deliberated to fulfil several sustainable development goals (SDGs). Graphical abstract: Image 1 Highlights: Impacts of crop residues in-situ firing in India were quantified and discussed. Biochar conversion of crop residues for its strategic management was discussed. Impact of pyrolysis process parameters on biochar yield & properties was reviewed. Biochar as a conventional & upcoming value-added product was comprehensively analysed. Crop residues – biochar system for the attainment of SDGs has been mapped.